Aplicação dos modelos conceituais da família FR para avaliação de software: o caso do Pergamum - Feitosa, Nayeli da Silva (2020)
The research aims to evaluate the Pergamum library automation system to understand if the search ferraments available in the system satisfy the needs of users defined by the tasks of users of the conceptual models Functional Requirements for Bibliographic Records (FRBR), Functional Requirements for Authority Data (FRAD) and Functional Requirements for Subject Authority Data (FRSAD). To this end, an exploratory research with a qualitative approach was used, which are justified here by the need to familiarize with the object of study and the characteristic of subjectivity in the identification of user tasks. With regard to procedures, the research is characterized as a case study, with the purpose of analyzing only the case of Pergamum, which is one among several Library Automation Systems. The results obtained from the application of the research indicate that SAB Pergamum don’t meets the user's action needs established by the user's tasks since, despite demonstrating numerous actions related to the tasks, the results of the search actions are still guided in standard bibliographic data not offering users new information retrieval strategies based on the usefulness of actions defined by user tasks. It also identifies that most of the resources present in Pergamum are linked to user tasks of a generalist nature, simple search activities. It signals the prospect of applying the same criteria used here for future analysis in other SABs and points out the absence of intuitive interfaces so that the user can carry out research independently.